Microstructure-mechanical property evaluation and deformation mechanism in Al added medium Mn steel processed through intercritical rolling and annealing - Sahoo, Biraj Kumar; Srivastava, Vikas Chandra; Mahato, B.; Ghosh Chowdhury, Sandip (Materials science & engineering. A, Structural materials : properties, microstructure and processing, 2021)
The present work investigates the microstructure evolution, mechanical properties and deformation mechanism in medium Mn high Al steel processed through intercritical rolling and subsequent intercritical annealing treatment at different temperatures. The annealed samples possessed a multi-phase microstructure consisting of intercritical ferrite/martensite, austenite and δ-ferrite. However, the morphology of the phases varied with annealing temperature. The result shows that annealing at a temperature of 730° and 780 °C led to the development of bimodal grain structure consisting of fine laths and equiaxed ultra-fine-grains (UFG) of ferrite-austenite; whereas annealing at 830 °C led to fully equiaxed coarse ferrite-austenite grains. An excellent combination of strength and ductility (product of ultimate tensile strength and elongation) as high as 56 GPa% was obtained in the 780 °C annealed sample. The chemical composition and grain size of austenite was found to be critical factors governing its stability. A mixture of lath and equiaxed austenite grains, having appropriate stability, in 780 °C annealed sample led to sustained four-stage strain hardening during deformation. Multiple work hardening mechanisms involving transformation induced plasticity (TRIP) effect, twin induced plasticity (TWIP) effect and discontinuous TRIP effect were found to occur sequentially in the equiaxed and lath-type austenite during the deformation that led to the extraordinary strength ductility combination.